Calculation Analysis and Test Verification of Transmission Efficiency of Rack Test Device for the Three Gorges Ship Lift - Li Youhua; Li Quancai; Liu Zhongming; Yu Feipeng; Liu Yuechan (Jixie chuandong)
The rack test device for the Three Gorges ship lift is mainly composed of four parts: driving gearbox,driving gear-rack,loading gear-rack and loading gearbox. In order to better calculate and analyze the transmission efficiency of the rack test device,through the establishing gearbox transmission efficiency calculation model,transmission efficiencies of the four parts and the transmission efficiency and the power consumption of the total whole unit are calculated respectively,the calculation results are contrastive analyzed by the input speed and torque,output speed and torque of the test data,the accuracy of calculation model and test data is verified,the research basis of transmission efficiency of gearbox and gear rack for low speed and load duty is established.